Czy słownictwo agrarne w utworach Jana Kochanowskiego jest słownictwem specjalistycznym? – analiza porównawcza na podstawie Gospodarstwa Anzelma Gostomskiego - Joanna Duska (Annales Universitatis Paedagogicae Cracoviensis. Studia Linguistica, 2020)
The aim of this article is to present agrarian terminology in Jan Kochanowski’s works and compare it with the vocabulary used by Anzelm Gostomski, the author of the oldest Polish handbook on gentry farming. Jan Kochanowski was a noble farm owner as well and Anzelm Gostomski lived at the same time as Jan Kochanowski.